Advances in discourse approaches - Dynel, Marta (Cambridge Scholars Pub., 2009)
Taboo words, Quentin Tarantino's films, humorous dialogues from "Sex and the City", witty advertising slogans, the Bible, Barack Obama's speeches, or legal discourse are only a few of the topics addressed in the volume. The study of discourse is a diversified and fast-developing field of language research, embracing methodological proposals, discourse analyses, comparative research, translation studies and teaching perspectives. Otherin each of the approaches, theoretical frameworks and postu ...